1995
DOI: 10.1021/ja00120a032
|View full text |Cite
|
Sign up to set email alerts
|

The Dendritic Box: Shape-Selective Liberation of Encapsulated Guests

Abstract: van den, E. M. M. (1995). The dendritic box, shape-selective liberation of encapsulated guests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
275
2
12

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(292 citation statements)
references
References 2 publications
3
275
2
12
Order By: Relevance
“…Most dendrimers are flexible enough to accommodate inclusion guests-indeed solvent molecules are generally thought to freely penetrate dendrimers-but they are also capable of rearranging themselves with significant volume collapse when solvent is removed. This collapse may leave guest molecules trapped inside the dendrimer, especially if favorable interactions exist, as in some ''dendritic micelles'' (37-41), or if the dendrimer structure has been rigidified to prevent their escape as in the ''dendritic box'' of Meijer and coworkers (42,43).…”
Section: Perspectivementioning
confidence: 99%
“…Most dendrimers are flexible enough to accommodate inclusion guests-indeed solvent molecules are generally thought to freely penetrate dendrimers-but they are also capable of rearranging themselves with significant volume collapse when solvent is removed. This collapse may leave guest molecules trapped inside the dendrimer, especially if favorable interactions exist, as in some ''dendritic micelles'' (37-41), or if the dendrimer structure has been rigidified to prevent their escape as in the ''dendritic box'' of Meijer and coworkers (42,43).…”
Section: Perspectivementioning
confidence: 99%
“…Due to the free-void volume located within the interior structure of the dendrimer, it can encapsulate guest molecules in its macromolecular interior, thus coating the nanoparticles and potentially preventing them from further oxidation and aggregation [22,23]. Moreover, it has been reported that the size of Ni nanoparticles formed through dendrimer templating depends on the metal-to-dendrimer ratio and generation of the dendrimer [24].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of end-group modifications are reported [24]. For the present hyper-Rayleigh scattering study, we have modified the poly(propylene imine) dendrimers with 4-dimethylaminophenylcarboxamide end-groups to yield DAB-…”
Section: Synthesis and Characterizationmentioning
confidence: 99%